ANALISIS RELIGIUSITAS, PEMAHAMAN PRODUK DAN SISTIM PEMBIAYAAN SYARIAH DENGANSIKAP PENGUSAHA - R. Ery Wibowo Agung Santosa; Andwiani Sinarasri (Universitas Muhammadiyah Semarang, 2015)
Along with the movement launched by the government of Islamic economics in 2013 it shows that Islamic economic sector shows an important role in sustaining economic growth. Islamic banks is one of the pillars of the economy which is expected to drive economic growth through strengthening capital. It is important for entrepreneurs to understand the products and financing mechanismssyariah. The syaria bank is expected can establish a joint venture partner with a productive entrepreneur. The main purpose of research iniadalah analyze the effect of understanding of the product and the financing system for the results in the Islamic bank with the attitude of entrepreneurtowards financing in Islamic banks through relegiusitas as pemoderating. It is hoped thiscan spur the growth of Islamic finance which have a direct impact on national economic growth. Thepopulation is Muslim businessman in Semarang. The data samples are taken using the method ofquestionnaire survey (self-report) and then analyzed using multiple regression to test the hypothesis ofthe absolute value of the difference Frucot and Shearon. Outcomes of this study are expected to add tothe enrichment of teaching materials for academics, increase the repertoire of research on Shariahbased banking system, contribute ideas and research results to the managers of Islamic banking, contribute ideas and empirical evidence to researchers about the continued operation of Islamic banks.Keywords: Relegiusitas, attitude,understanding